RESTRUKTURISASI ORGANISASI SEBAGAI UPAYA PENINGKATAN EFEKTIFITAS KERJA KARYAWAN AK. MAPINDO - Ni Putu Lindawati; Bagus Putu Ekadharma Susila (Journal of Applied Management and Accounting Science, 2022)
This study aims to analyze organizational restructuring in AK. MAPINDO as an effort to improve employee work effectiveness. The analysis technique used is SWOT analysis, namely analyzing internal factors and external factors that exist within the AK environment. MAPINDO. This research is a qualitative research with data sources used are primary data and secondary data. Data collection techniques used through observation (observation), interviews (interviews), documentation (documentation) and literature study (literature study). The informants in this study were all AK senates. MAPINDO (Indonesian Hospitality Management Community Academy) which has 7 members. The results of the analysis show that the strength factors include: increasing education, productive age, work experience, organizational experience and high morale; Weakness factors include: more responsibility, delegation of tasks and responsibilities to new officials, adjustments to new assignments, new positions in the organizational structure, and adjustments to bureaucratic lines, opportunity factors include: supervision, work evaluation, increased resource efficiency management, work innovation and ease in achieving goals: threat factors include: workload, work stress, decreased motivation and work environment. As for the organizational restructuring of AK. MAPINDO in relation to efforts to increase the effectiveness of employee work, can be done by directing employees in achieving organizational goals, adjusting job descriptions and responsibilities to increase employee competence and provide opportunities for employees widely to increase work innovation.